Vitamin D receptor gene polymorphisms in children with kidney stone disease - ALPAY, HARİKA; GÖKCE, İBRAHİM; DELİL, KENAN (TURKISH J PEDIATRICS, 2017)
Kidney stone disease has a multifactorial etiology involving the interaction of genetic and environmental factors. There is an increased risk of stone formation in the relatives of idiopathic stone patients, which can be explained up to 60% by genetic factors. This study was conducted to explore the association of vitamin D receptor (VDR) gene polymorphisms with the risk of urolithiasis (UL) in Turkish children. We investigated the VDR gene polymorphisms: ApaI, BsmI, TagI, Cdx2, FokI, in 52 children (26 boys, 26 girls) with UL and in 51 healthy children (22 boys, 29 girls) without UL. Apa I, BsmI, TagI, Cdx2, FokI genotypes were analyzed by Apa I, BsmI, TagI, Cdx2, FokI restriction enzyme digestion, respectively. The resulting alleles are designated as ABTCF (ApaI, BsmI, TagI, Cdx2, and FokI restriction site is absent), or abtcf (ApaI, BsmI, TagI, Cdx2, FokI restriction site is present), respectively. Genotype and allele frequencies were calculated, and the association with UL, hypercalciuria and hypocitraturia was investigated. Our data provide no statistically significant evidence for an association between UL and VDR ApaI, BsmI, TagI, Cdx2, and FokI genotype and allele frequencies. Patients with hypocitraturia and hypercalciuria were compared with the control group and no statistically significant difference was detected in terms of VDR gene ApaI, BsmI, TagI, Cdx2, and FokI polymorphisms and allele frequencies. Our data suggest that the VDR ApaI, BsmI, TagI, Cdx2, and FokI polymorphisms do not indicate a significant risk for UL.
Keywords: urolithiasis; hypercalciuria; hypocitraturia; vitamin D receptor; BONE-DENSITY; UROLITHIASIS; NEPHROLITHIASIS; CALCIUM; RISK; SUSCEPTIBILITY; HYPERCALCIURIA; ASSOCIATION; GENOTYPE